2014
DOI: 10.1007/s40122-014-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cognitive and Psychomotor Performance in Patients with Fibromyalgia Syndrome

Abstract: IntroductionPatients with fibromyalgia syndrome (FMS) generally present with chronic widespread pain, accompanied by a range of additional and non-specific symptoms, such as fatigue, disturbed sleep, and cognitive dysfunction, which tend to increase with overall severity. Previous studies have shown moderate cognitive impairment in patients with FMS, but there are few valid data explicitly assessing the relevance of these findings to everyday functions, such as driving ability. Therefore, we studied patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
1
16
0
3
Order By: Relevance
“…As a result, many studies have evidenced cognitive impairment in patients with fibromyalgia compared with control groups, with fibromyalgia patients mainly exhibiting problems with working memory processes and/or in their attentional and executive domains, as well as in processing speed [ 3 8 ]. However, other studies have failed to find any impaired performance in the cognitive functions of these patients [ 9 12 ]. A couple of recent meta-analytical reviews undertaken with a chronic pain population have provided evidence of impairment of working memory and also of three other components of executive functions: response inhibition, complex executive function and set shifting [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 85%
“…As a result, many studies have evidenced cognitive impairment in patients with fibromyalgia compared with control groups, with fibromyalgia patients mainly exhibiting problems with working memory processes and/or in their attentional and executive domains, as well as in processing speed [ 3 8 ]. However, other studies have failed to find any impaired performance in the cognitive functions of these patients [ 9 12 ]. A couple of recent meta-analytical reviews undertaken with a chronic pain population have provided evidence of impairment of working memory and also of three other components of executive functions: response inhibition, complex executive function and set shifting [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 85%
“…Several studies have coincided in identifying the existence of cognitive dysfunction in fibromyalgia and in emphasizing problems associated with executive functions and, more specifically, with working memory processes and attentional and executive control [4][5][6][7]. However, some authors have failed to find such impaired performance in these components [8][9][10], while others have even concluded that the cognitive dysfunction observed in these patients could be explained by concurrent symptoms of depression [11,12].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Clinically, the objective consequences of dyscognition in fibromyalgia are not clear ( Shmygalev et al, 2014 ). Cognitive deficits are not overtly obvious to medical observation, certainly far less than what is seen in pathologically-defined neuropsychiatric dementias such as Alzheimer's disease and vascular dementia.…”
Section: Introductionmentioning
confidence: 99%